Pemberian Air Rebusan Serai pada Lansia Penderita Nyeri Rheumatoid Arthritis di Panti Sosial Tresna Werdha Budi Luhur Jambi - Rahmadhani, Dwi Yunita; Yesni, Marnila; Fajri, Jufri Al; Maimaznah, Maimaznah; Pebrianti, Dwi Kartika; Putri, Miko Eka (Universitas Baiturrahim, 2025)
Elderly individuals are defined as those aged 60 years and above. In general, aging is accompanied by a gradual decline in biological, psychological, social, and economic functions. One of the most common health problems among the elderly is Rheumatoid Arthritis (RA). RA is an autoimmune disease characterized by inflammation in the joints, particularly in the hands and feet, leading to pain, swelling, and often joint damage. Non-pharmacological therapy management can be applied to reduce pain and inflammation, maintain joint function, and prevent deformities. These include resting painful joints, maintaining an ideal body weight, ensuring adequate nutrition, applying warm compresses, and performing physiotherapy. Based on these considerations, this community service activity aimed to improve the health quality of the elderly and reduce pain intensity through the application of warm water and lemongrass compress therapy. The activity was conducted from March to August 2023, specifically on July 12–13, 2023, at Panti Sosial Tresna Werdha Budi Luhur Jambi. The participants consisted of 39 individuals (elderly residents and staff). The method used was direct simulation and demonstration on elderly participants experiencing pain. The results of the activity showed a reduction in pain intensity among all elderly participants following the intervention. The outcomes of this community service included an overall improvement in the quality of life of the elderly, a reduction in joint pain complaints, enhanced knowledge regarding herbal-based non-pharmacological therapy, and the strengthening of holistic nursing approaches in the elderly care setting. Additionally, this activity is planned for publication in a nationally accredited journal as part of the dissemination of community empowerment results.